Terahertz Characteristics of Magnetic Fluid Based on Microfluidic Technology - Zhao, Xinyuan; Wang, Guoyang; Shao, Siyu; Meng, Qinghao; Wang, Jiahui; Zhang, Sijia; Su, Bo; Zhang, Cunlin (International Journal of Optics, 2021)
Magnetic fluid is a new functional material with both liquid fluidity and solid magnetism, which has important application value in medicine, biology, and so on. In this study, terahertz technology and microfluidic technology were combined to investigate the terahertz transmission characteristics of a magnetic fluid in different magnetic fields and different electric fields. In the external magnetic field, the intensity of the terahertz spectrum increased with an increase in the magnetic field intensity, and the response to the magnetic field in different directions was different. Under the applied electric field, the intensity of the terahertz spectrum decreased with an increase in the electric field intensity. This method is convenient for studying the terahertz characteristics of magnetic fluid and provides technical support for in-depth studies of magnetic fluid.